An integration of Solow's growth and Dixit-Stiglitz's monopolistic competition models - Wei-Bin Zhang (SPOUDAI - Journal of Economics and Business, 2018)
This study proposes an economic growth model with perfectly competitive and monopolistic competitive market structures. Our model is based on two core models in two mainstreams of economic theories. One is the Solow model in neoclassical growth theory. The other one is the Dixit-Stiglitz model of monopolistic competition. The unique contribution of this research is to integrate the two models in a comprehensive framework. It endogenously determines profit which is equally distributed among the homogeneous population. We examine the role of perfect competition and monopolistic competition in economic growth. We build and then simulate the model. We find a unique equilibrium point and confirm stability. We plot the motion of the economy and conduct comparative dynamic analyses to get some insights into the complexity of economic growth.
Keywords: D11; O41; L13; 330; Solow model; monopolistic competition; Dixit-Stiglitz model; wealth accumulation; profit